The Role and Clinical Correlates of Complex Post-traumatic Stress Disorder in People With Psychosis - Panayi, Peter; Berry, Katherine; Sellwood, William; Campodonico, Carolina; Bentall, Richard P.; Varese, Filippo (Frontiers in Psychology, 2022)
Traumatic experiences and post-traumatic stress are highly prevalent in people with psychosis, increasing symptom burden, decreasing quality of life and moderating treatment response. A range of post-traumatic sequelae have been found to mediate the relationship between trauma and psychotic experiences including the ‘traditional’ symptoms of post-traumatic stress disorder (PTSD). The International Classification of Diseases-11th Edition recognises a more complex post-traumatic presentation, complex PTSD (cPTSD), which captures both the characteristic symptoms of PTSD alongside more pervasive post-traumatic sequelae known as ‘disturbances in self-organisation’ (DSOs). The prevalence and impact of cPTSD and DSOs in psychosis remains to be explored. In the first study of this kind, 144 participants with psychosis recruited from North West United Kingdom mental health services completed measures assessing trauma, PTSD and cPTSD symptoms and symptoms of psychosis. Forty-per-cent of the sample met criteria for cPTSD, compared to 10% who met diagnostic criteria for PTSD. PTSD mediated the relationship between trauma and positive symptoms; DSOs did not contribute to explaining this relationship. Both PTSD and DSOs mediated the relationship between trauma and affective symptoms but did not explain a significant proportion of variance in negative symptoms. Cognitive and excitative symptoms of psychosis did not correlate with trauma, PTSD or DSO scores. This findings indicate the possible value of adjunct therapies to manage cPTSD symptoms in people with psychosis, pending replication in larger epidemiological samples and longitudinal studies.